2014
DOI: 10.1007/s11191-014-9692-z
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Discipline-Culture Framework of Physics Knowledge: A Teaching Experience in Italian Secondary School

Abstract: The paper deals with physics teaching/learning in high school. An investigation in three upper secondary school classes in Italy explored the reactions of students to a structuring lecture on optics within the discipline-culture (DC) framework that organises physics knowledge around four interrelated fundamental theories of light. The lecture presented optics as an unfolding conceptual discourse of physicists regarding the nature of light. Along with the knowledge constructed in a school course of a scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…A similar finding was reported by Levrini et al. () for Italian upper secondary students after a teaching intervention on optics and the nature of light where HPS aspects had a central role. Despite this interest and motivation, however, students in our investigation did not necessarily see HPS aspects as learning goals in their own right.…”
Section: Discussionsupporting
confidence: 89%
“…A similar finding was reported by Levrini et al. () for Italian upper secondary students after a teaching intervention on optics and the nature of light where HPS aspects had a central role. Despite this interest and motivation, however, students in our investigation did not necessarily see HPS aspects as learning goals in their own right.…”
Section: Discussionsupporting
confidence: 89%
“…The course begins with the contemporary view of spacetime, motion, and gravity, rather than starting with the Newtonian mechanistic view. Levrini (1999) suggests that introducing the contemporary ideas about space and time into physics education early on can provide a powerful means of drawing learners into the study of physics because it interrogates “pre-scientific” concepts of space and time that have historically been at the center of cultural debates, and thus of general human interest. More importantly, space and time are historically of concern to other disciplines such as art, literature, and philosophy and thus can be a powerful bridge to other subjects, allowing for a comparison of the physics ways of looking at space with other points of view (Levrini, 1999).…”
Section: The Experimentsmentioning
confidence: 99%
“…We have shown elsewhere that the teaching approach in ReleQuant with small-group discussions can be productive in the sense that they deepen students' understanding and make them ask new questions (Bungum et al, 2018). Along similar lines, Levrini et al (2014) observed that Italian upper secondary physics students refined their epistemological positions after a teaching intervention on optics and the nature of light where historical and philosophical aspects had a central role. The findings resonate with Krijtenburg-Lewerissa et al (2017) recommendations for quantum physics teaching strategies, which include emphasis on interpretations along with active learning methods.…”
Section: Students' Epistemological Reflections and Notions About The Nature Of Sciencementioning
confidence: 67%